Integrating Tax Sanctions and Trust Through Tax Awareness to Explain MSME Taxpayer Compliance: The Theory of Planned Behavior Approach - Amah, Nik; Ermawati, Nanik; Pratiwi, Desy Nur; Pramudyawati, Anggita Putri (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Abstract Introduction: Taxes are a major source of state revenue, but the level of tax compliance among MSMEs in Indonesia remains relatively low despite this sector's significant contribution to the economy. This study aims to analyze behavioral factors influencing MSME taxpayer compliance using the Theory of Planned Behavior perspective. Background Problem: The gap between the growth in the number of MSMEs and low tax compliance indicates a behavioral problem. Therefore, the research question is: What is the role of tax sanctions and trust in the government in influencing MSME taxpayer compliance through tax awareness? Novelty: This study offers novelty by integrating law enforcement-based and trust-based compliance approaches by examining the mediating role of tax awareness, a phenomenon that has not been widely studied simultaneously in the MSME context. Research Method: This study uses a quantitative, causal, and associative approach with primary data in the form of questionnaires from 142 MSMEs in Madiun City. Data analysis was conducted using Smart Partial Least Squares (Smart-PLS) through testing of measurement and structural models. Findings: The results of this study indicate that tax sanctions and trust in the government have a positive influence on taxpayer awareness and tax compliance, and tax awareness is proven to significantly mediate this relationship. Conclusion: MSME tax compliance is influenced not only by sanction enforcement but also by psychological factors such as trust and tax awareness. These findings imply that tax policy needs to combine regulatory approaches and building public trust to sustainably improve tax compliance.